Anaerobic Bacteria from Surgical Site Infections and Its Antibiotic Susceptibility Pattern in Eastern Nepal: A Prospective Study - Dewasy, Bijoylakshmi; Tuladhar, Reshma; Singh, Randhir Kumar; Singh, Praveer Raj; Pokharel, Hanoon P; Singh, Anjana (Birat Journal of Health Sciences, 2025)
Introduction: Surgical site infections (SSIs) are categorized into three types: superficial, deep, and organ space infections. Inadequate anaerobic coverage during postoperative infections can lead to treatment failures, longer hospital stays, and increased morbidity; updated susceptibility data are essential for optimizing antimicrobial selection.Objectives: To isolate and identify anaerobic bacteria from surgical site infections and to assess their antibiotic susceptibility pattern. The study also aimed to compare the current findings (phase II) with those of a previous phase (phase I) to observe any changes in bacterial profile or resistance trends.Methodology: This is an observational, cross-sectional analytical study conducted in Birat Medical College Teaching Hospital, Morang, Nepal from October 2021 to December 2024. This research investigates up on 641 patients with SSIs in phase I and 701 patients in phase II who underwent surgery during the study period. . The collection and analysis of wound specimens for anaerobic bacterial culture, employing both conventional and rapid isolation methods were carried out. Logistic regression was used to examine the relationship between host risk factors and blood parameters, and the antimicrobial resistance of anaerobic bacteria was evaluated using the agar dilution method. Ethical clearance was obtained from Nepal Health Research Council and written consent were taken from all participants under study.Results: The study found  a remarkable Surgical Site Infections (12.3%) with anaerobic SSIs (5.7%).  Pus specimen was the most frequently collected in both  phases. The infection rate was significantly higher in elective surgeries (77.5%) compared to emergency surgeries (22.5%). A significant association was observed between comorbidities and infection sites in anaerobic culture-positive SSIs. The primary bacterial isolation identified was Bacteroides fragilis, followed by Bacteroides thetaiotamicron, Clostridium perfringens, and Peptoniphilus asaccharolyticus. Alarmingly high (50%) isolation exhibited resistance to metronidazole and tetracycline.Conclusion: This study emphasized the updated surgical antibiotic prophylaxis and aimed at improving the management of SSIs in a phase II study.